2009
DOI: 10.4103/0975-1483.55744
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory activity of ethanolic leaf extracts fromAdenanthera pavonina(l) in Rats

Abstract: Preparation of ethanolic extract of Adenanthera pavonina The leaves were shade-dried and made into a coarse powder which was passed through a 40-mesh sieve to get a uniform particle size and then used for extraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…[19][20][21] The study reveals that the extract has exhibited dose dependent activity and is at par to previous studies 10 due to presence of steroids, alkaloids and triterpenoids in the extract. 11,[13][14][15] Migration of WBC during the process of inflammation is a biological marker in inflammatory studies. On assessing the hematological parameters it was seen that at both the doses of extract there is decrease in leucocyte and PMN count depicting that the action is not dose dependent.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[19][20][21] The study reveals that the extract has exhibited dose dependent activity and is at par to previous studies 10 due to presence of steroids, alkaloids and triterpenoids in the extract. 11,[13][14][15] Migration of WBC during the process of inflammation is a biological marker in inflammatory studies. On assessing the hematological parameters it was seen that at both the doses of extract there is decrease in leucocyte and PMN count depicting that the action is not dose dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Administration of indomethacin and the plant extract was done by p.o. route 13,14 . A mark was made at the ankle up till which the paw was dipped and paw volume was measured at interval of 1 h, 2 h, 3 h and 5 h using a plethysmometer.…”
Section: Carrageenan Induced Paw Edema In Ratsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, results generated from this study demonstrated the antiinflamatory and analgesic potential effects of the methanolic extract obtained from A. pavonina seeds (Olajide et al, 2004). Using the ethanolic extract from A. pavonina's leaves, Mayuren and Ilavarasan (2009) evaluated their antiinflammatory effects in Wistar rats at doses of 250 and 500 mg/kg in carrageenan-induced hind paw edema tests. Also, the chronic inflammation was measured using the cotton pellet-induced granuloma formation assay.…”
Section: Anti-inflammatory Activitymentioning
confidence: 73%
“…Other stigmasterol glucosides, including octacosanol and dulcitol, have also been reported in the leaves of this plant (Mayuren and Ilavarasan, 2009;Moniruzzaman et al, 2015). Zeid et al (2012) also isolated at the first time three triterpenoid compounds identified as 22-hydroxy hopan-3-one (A), 24-methylene cycloartenol (B) and betulinic acid (C) (Appendix A4).…”
Section: Phytochemical Analysis Of Leavesmentioning
confidence: 77%